Potensi Daun Jambu Air (Syzygium aquem) sebagai Fitofarmaka : Literature Review - Febrianti, Arlin; Susianti, Susianti; Kusumaningtyas, Intan; Mustofa, Syazili (CV. Jasa Sukses Abadi, 2024)
Traditional medicine widely utilizes plant extracts from various parts of plants due to their secondary metabolite content, which possesses therapeutic effects. One plant with high pharmacological potential is the water apple leaf (*Syzygium aqueum*), belonging to the Myrtaceae family and commonly found in tropical regions such as Indonesia, Malaysia, and India. Water apple leaves have been used as phytopharmaceuticals because they contain various bioactive compounds that can be extracted and utilized for treating different diseases. The active compounds commonly found in water apple leaves include alkaloids, flavonoids, steroids, triterpenoids, and coumarins. Studies have shown that water apple leaf extracts exhibit various pharmacological activities, including antibacterial, antioxidant, anti-inflammatory, anticancer, antimicrobial, and antidiabetic properties. Additionally, the bioactive compounds in water apple leaves have the potential to be further developed as natural therapeutic agents for treating degenerative diseases and infections. This pharmacological potential positions water apple leaves as a promising phytopharmaceutical candidate for development in the pharmaceutical and healthcare industries. However, further research is required to explore the mechanisms of action, efficacy, and potential toxicity of the active compounds in water apple leaves. A comprehensive study in this area will enable the optimization of water apple leaves as a safe and effective natural therapy for various diseases.